Leadership and Performance of Teachers and Employees of SMK Sunan Drajat Lamongan - Ulum, Miftachul; Mun'im, Abdul (Multidisciplinary Journal of Education , Economic and Culture, 2023)
This study aims to determine the effect of leadership style on the work performance of teachers and employees at SMK Sunan Drajat Lamongan. Quantitative research method involving 98 respondents using the validity test, reliability test and multiple regression analysis. The results of research at SMK Sunan Drajat Lamongan showed the magnitude of the positive influence between the influence of leadership style on the work performance of teachers and employees at SMK Sunan Drajat Lamongan. The correlation coefficient value of 0.876 indicates a positive relationship between leadership style and employee performance at SMK Sunan Drajat Lamongan. While the coefficient of determination (R2) is 76.7% indicating the magnitude of the contribution of leadership style to work performance